Open Microfluidic Cell Culture in Hydrogels Enabled by 3D-Printed Molds - Madison O’Brien; Ashley N. Spirrison; Melati S. Abdul Halim; Yulai Li; Adrian Neild; Catherine Gemrich; Reza Nosrati; Luis Solorio; Max M. Gong (Bioengineering)
Cell culture models with tissue-mimicking architecture enable thein vitro investigation of cellular behavior and cell–cell interactions. These models can recapitulate the structure and function of physiological systems and can be leveraged to elucidate mechanisms of disease. In this work, we developed a method to create open microfluidic cell cultures in vitro using 3D-printed molds. The method improves sample accessibility, is simpler to manufacture than traditional closed microfluidic cell culture systems and requires minimal specialized equipment, making it an attractive method for cell culture applications. Further, these molds can generate multiple tissue-mimicking structures in various hydrogels, including blood vessel mimics using endothelial cells (HUVECs). Various geometries were patterned into agarose, gelatin, and collagen type I hydrogels, including star-shaped wells, square wells, round wells, and open channels, to demonstrate the versatility of the approach. Open channels were created in collagen with diameters ranging from 400 µm to 4 mm and in multiple collagen densities ranging from 2 mg/mL to 4 mg/mL. To demonstrate the applicability of our approach for tissue modeling, blood vessel mimics were generated in open channels with diameters of 800 µm and 2 mm, with high cell viability (>89%) for both dimensions. The vessel mimics were used to study the effects of hypoxia on cell viability and CD31 expression by subjecting them to a reduced-O2 environment (∼16% <semantics>O2</semantics>). As compared to normoxia conditions, vessel mimics under hypoxia had a reduction in cell viability by 8.3% and CD31 surface expression by 7.4%. Overall, our method enables the generation of different geometries in hydrogels and the development of in vitro tissue mimics for biological applications.